Population parameters and the relationships between environmental factors and abundance of the Acetes americanus shrimp (dendrobranchiata: Sergestidae) near a coastal upwelling region of Brazil - dos Santos, Ana Paula Freitas [UNESP]; Simões, Sabrina Morilhas [UNESP]; Bochini, Gabriel Lucas [UNESP]; Costa, Cinthia Helena [UNESP]; da Costa, Rogerio Caetano [UNESP] (FapUNIFESP (SciELO), 2015)
The population dynamics of Acetes americanus was investigated, focusing on the sex ratio, individual growth, longevity, recruitment and relationship between abundance and environmental factors in the region of Macaé, strongly influenced by coastal upwelling. Otter trawl net samplings were performed from July 2010 to June 2011 at two points (5 m and 15 m). Nearly 19,500 specimens, predominantly females (77.15%), were captured. Their sizes, larger than that of males, indicated sexual dimorphism. Shrimps at lower latitudes present larger sizes and longer longevity than those from higher latitudes. This difference is probably due to low temperatures and high primary productivity. Though no statistical correlation was found between abundance and environmental factors, the species was more abundant in temperatures closer to 20.0° C and in months with high chlorophyll-a levels. Due to the peculiar characteristics of this region, A. americanus showed greater differences in size and longevity than individuals sampled in other studies undertaken in the continental shelf of Southeast Brazil.
Keywords: Decapoda; Growth; Longevity; Macaé - RJ; Pelagic